A todas las que ya no están feminicidios en el Huila y Tolima durante los años 2015 al 2018 - Montenegro Losada, Liz Giomaira; Sánchez Falla, Carolina; Celis Ferreira, Claudia Lorena; Rivera Quintero, Katherine; Sánchez Barrera, María Elva; Campos Ramírez, Nelly; Guzmán Torres, Carolina; Ávila Sogamoso, Daniela; Manrique Pérez, Leidy Marcela; Guzmán Álvarez, Lidsady Halaineed; Redondo Licona, Miryan Daniela; Valencia Riveros, María Alejandra; et al. (Sello Editorial UNAD, 2023)
Feminicide has become a problem of general interest due to its high impact on the Colombian population; in this sense, this phenomenon was studied to characterize it in the departments of Huila and Tolima, which is why for the researchers it is essential to make this problem visible, pointing out the conditions framing violence against women from this macho culture that prevails in the region and country. The topic is of special interest since a review of press articles, epidemiological reports, local statements, and research on femicide in the two departments was carried out, seeking to make this phenomenon more visible to show the country’s reality so that it can be reported on. The results show that there is no research on the subject, which makes it possible to initiate a database with studies on femicide. Similarly, the National Institute of Legal Medicine and Forensic Sciences (2016) considers that the data described on homicide in 2015 and in previous years have decreased in magnitude over the years. The analysis of the variables realizes that the risk factors triggering the violent events that determine homicide have not been neutralized, reduced, or controlled, considering that public policy on security and citizen coexistence has been insufficient.
Keywords: Frauenmord; Kolumbien; Feminicidio; investigación; violencia de género; protección a la mujer